Monsieur Ibrahim et les fleurs du Coran [videorecording (DVD)] - Dupeyron, François; Sharif, Omar, 1932-2015; Boulanger, Pierre, 1987-; Melki, Gilbert; Renauld, Isabelle; Naymark, Lola; Suarez, Anne; Chevrin, Rémy, 1963-; Bouchard, Catherine; Coupez, Fabien; Schmitt, Éric-Emmanuel (Sony Pictures Classics ; Columbia TriStar Home Entertainment, 2004)
An elderly Turkish Muslim grocer befriends a lonely teenage Jewish boy in a working class section of Paris.